A new molineid (Nematoda: Trichostrongylina) parasite of dasypus hybridus (Xenarthra: Dasypodidae) from Argentina - Ezquiaga, María Cecilia (2012)
Delicata abbai n. sp. collected from the small intestine of the southern long-nosed armadillo, Dasypus hybridus, from Argentina is herein described. This new species is characterized by vulvar opening within second half of body length, female tail conical, ending bluntly with a terminal spine, complex spicules, presence of a bursal membrane supported by 2 small rays, and a synlophe with bilateral symmetry and 26 cuticular ridges. By the morphology of the caudal bursa, caudal end of female, and shape of spicules, the new species resembles Delicata cameroni Travassos, 1935 and Delicata variabilis Travassos, 1935. However, it differs from D. cameroni by having rays 5 and 6 diverging more proximally, rays 8 shorter than the dorsal ray, and spicules with a different shape. Delicata abbai n. sp. is distinguished from D. variabilis mainly by the spicules, which have a different shape and proportion of their constitutive parts. This is the first report of a species of Delicata in Argentina.